ANALISIS RISIKO PRODUKSI PADI PADA LAHAN PETANI BINAAN PROGRAM MAKMUR DI KABUPATEN KARAWANG - Syadiah, Siti Maulida; Sulandjari, Kuswarini; Nur'azkiya, Luthfi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Program Makmur for rice commodities has been implemented in Karawang Regency since 2021 and there has been an increase in productivity. However, in the Program Makmur for planting season 1 in April–July 2022, rice productivity in Pedes and Tempuran Districts was the lowest compared to other districts. The average productivity of rice in Pedes District is 4.75 tons/ha and in Tempuran District is 3.96 tons/ha. The purpose of this study was to identify production risks, measure the severity of production risks, and analyze the main sources of risk faced by rice farmers who are partners with the Program Makmur. This research is a quantitative and qualitative research. The research data is in the form of primary data and secondary data. Primary data collection by interview techniques using questionnaires and observation. Secondary data was obtained from the Central Bureau of Statistics and PT Pupuk Kujang. There were 33 research respondents consisting of 30 farmers who were determined based on saturated sampling, 1 Agronomist Program Makmur and 1 agricultural extension agent in Pedes District and 1 agricultural extension agent in Tempuran District. Instrument test using validity test and reliability test. Data analysis methods used are Fishbone diagrams, Failure Mode and Effect Analysis (FMEA), and Pareto diagrams. The results of this study show that there are 19 sources of production risk, including 5 risks originating from the environment, 5 risks originating from materials, 3 risks originating from humans, and 6 risks originating from methods. The highest Risk Priority Number (RPN) value is found in risk sources originating from the environment, namely pest and disease attacks with an RPN of 533.61. There are 9 sources of risk with the highest RPN values to be prioritized for risk management.